2018
DOI: 10.1093/ofid/ofy118
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Stress Response to Varicella-Zoster Virus Infection of Human Skin Includes Highly Elevated Interleukin-6 Expression

Abstract: BackgroundThe infectious cycle of varicella-zoster virus (VZV) after reactivation from the dorsal root ganglia includes replication and assembly of complete enveloped virions in the human skin to cause the characteristic herpes zoster (shingles).MethodsTo pursue studies of innate immunity to VZV infection, we have adapted a fetal skin organ culture model to a human neonatal foreskin explant model.ResultsAbundant expression of VZV IE62, gE, and gC was visualized by confocal microscopy while numerous enveloped v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…Interestingly, we demonstrated a very high IL-6 protein levels (ϳ30,000 pg/ml) in the footpad of PRV-Becker-infected mice. This result strongly correlates with a recent study, which demonstrated the same exact concentration of IL-6 in human skin explant cultures after VZV infection (27). Thus, these findings support the fact that VZV and PRV have very similar innate immune responses to infection of skin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we demonstrated a very high IL-6 protein levels (ϳ30,000 pg/ml) in the footpad of PRV-Becker-infected mice. This result strongly correlates with a recent study, which demonstrated the same exact concentration of IL-6 in human skin explant cultures after VZV infection (27). Thus, these findings support the fact that VZV and PRV have very similar innate immune responses to infection of skin.…”
Section: Discussionsupporting
confidence: 91%
“…Similar lethal systemic inflammatory responses have also been reported during dengue virus, Sindbis virus, and SARS-CoV infections (24)(25)(26). Interestingly, a recent study also demonstrated that VZV infection induces high levels of IL-6 transcription and protein production in human skin explant cultures (27).…”
Section: Introductionsupporting
confidence: 67%
“…VZV is highly contagious and can be transmitted through respiratory droplets or direct contact with infected skin lesions [9][10][11]. VZV is neurotropic and which can be lurking in the neurons of the posterior root ganglia of the spinal cord for a long time after infection.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-2 genital infection carries a three-fold increased risk for acquisition and transmission of HIV [8]. The common cold sores caused by HSV-1 and the genital herpes lesions caused by HSV-2 are not life-threatening conditions, but serious pathology can result from infections of the cornea (keratitis) or central nervous system (encephalitis), and infection of newborns or immunocompromised individuals can result in severe disseminated disease [9], and Varicella-zoster virus (VZV) or human herpes virus 3 (HHV-3) is 1 of 9 human herpes viruses [10]. VZV is a human pathogen that spreads to children as varicella or chicken pox and reemerges later in life as zoster or shingles [11,12].…”
Section: Introductionmentioning
confidence: 99%